Government Communication and Information Activists: The Struggles to Build Political Legitimacy among Young Citizens - Jave, Iris (2017)
This article is an approximation to the analysis of the transit from electoral communication to government communication, a period that is usually addressed as two differentiated dimensions, but which can be enhanced to contribute to the governments’ legitimacy and their relationship with citizens (information activists). After measuring university students and professionals’ electoral preferences in Lima, we conclude that the articulation of electoral and government communication consists not only in recognizing the expectations of these citizens, widely expressed during political campaigns, but also in consolidating dialogue channels during the government administration.